Organizational Agility, Open Innovation, and Business Competitive Advantage: Evidence from Culinary SMEs in Indonesia - Hardi Mulyono; Abd. Rasyid Syamsuri (Universitas Pendidikan Ganesha, 2023)
Some problems that are often faced by small and medium industry players are the low ability of SMEs to explore opportunities, and the low ability of SMEs to innovate in business. Therefore, the purpose of this study is to examine the influence of organizational agility and open innovation on competitive advantage in culinary SMEs in Medan. This study used quantitative methods. The subjects in this study were employees and owners of the culinary industry in Medan City as many as 218 respondents. The sampling technique is carried out by accidental sampling method. The data was processed by structural methods of modeling equations, and using the IBM Amos Program. The results showed that there was a positive and significant influence between organizational agility and corporate open innovation. The findings also prove that organizational agility and open innovation can predict the competitive advantage of the culinary industry in Medan City positively and significantly. The results also found that open innovation mediates the influence of organizational agility on the competitive advantage of the culinary industry in Medan. In other words, open innovation is proven to significantly mediate those that form or create strong links between organizational agility and competitive advantage. We provide suggestions to improve organizational agility, and unlock innovations in the culinary industry in Medan City to improve business competitiveness.